2003
DOI: 10.1016/s1010-7940(02)00827-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obesity on mid-term survival following coronary artery bypass surgery

Abstract: Although in-hospital mortality after CABG does not seem to be adversely affected by obesity there appears to be a significant increase in mortality in obese patients during a 4-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 16 publications
2
47
3
3
Order By: Relevance
“…Like Kuduvalli et al we also could not find a significant difference for postoperative myocardial infarction [16]. This is in contrast with the study by Prasad et al where obese patients were more likely to have a myocardial infarction [10].…”
Section: Morbiditycontrasting
confidence: 82%
“…Like Kuduvalli et al we also could not find a significant difference for postoperative myocardial infarction [16]. This is in contrast with the study by Prasad et al where obese patients were more likely to have a myocardial infarction [10].…”
Section: Morbiditycontrasting
confidence: 82%
“…3 In ENRICHD, prior to multivariable correction, a similar effect was observed. [5][6][7][8][9] After correction for confounders, the association disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients undergoing revascularization have shown better outcomes or no increased risk in overweight and obese patients. [2][3][4][5][6] Many studies have shown either no association or a favorable effect of obesity in patients with MI; others only a modest association with recurrent events. 1,[7][8][9][10] A pooled analysis of CAD patients has shown an inverse J curve with patients with BMI between 30-35 having the lowest long-term mortality.…”
Section: Introductionmentioning
confidence: 99%
“…14) Other short-term adverse effects of blood transfusions in cardiac surgical patients have been documented well, but few studies have assessed long-term survival. 15,16) Despite all available evidence, transfusion practices vary substantially. 18,24) Deciding when a patient requires transfusion varies significantly among intensivists, anesthetists, and cardiac surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…13) It also has been suggested that the BMI cutoff point for overweight or obesity in the Chinese population should be lower than WHO standards. 14) Therefore, we adopted the Chinese BMI cutoff values proposed by the Working Group on Obesity in China (WGOC) 15) and described in the Guidelines for Prevention and Control of Overweight and Obesity in Chinese Adults 16) to define overweight or obesity, as follows: BMI <18.5 kg/m 2 (underweight), 18.5≤ BMI <24 kg/m 2 (normal weight), 24≤ BMI <28 kg/m 2 (overweight), and BMI ≥28 kg/m 2 (obese). Because few patients were in the underweight group, we combined the underweight and normal weight groups (<24 kg/m 2 ).…”
Section: Study Populationmentioning
confidence: 99%